MicroRNA-224 orchestrates BMP and TGFβ signaling and is a therapeutic target in preclinical pulmonary arterial hypertension - Olympia Bikou; Aymen Halouani; Yifei Sun; Malik Bisserier; Clemens Eisenacher; Samar A. Antar; Petros Avramopoulos; Carlos G. Santos-Gallego; Catherine Swarts; Erik Kohlbrenner; Kiyotake Ishikawa; Marc Humbert; et al. (Science Translational Medicine, 2026)
Pulmonary arterial hypertension (PAH) is a progressive pulmonary vascular disease that leads to right heart failure and ultimately death. Therapeutic options targeting the underlying mechanisms of the disease are urgently needed. MicroRNAs (miRs) have emerged as critical regulators of cardiovascular homeostasis and disease. Here, we identified microRNA-224-5p (miR-224) as a regulator of pulmonary vascular remodeling and delineate its mechanism of action in PAH. miR-224 expression was increased in the lungs of patients with PAH and across multiple experimental models of pulmonary hypertension, including mouse, rat, and pig models, as well as in pulmonary arterial smooth muscle cells (PASMCs) isolated from patients with PAH. In vitro, miR-224 overexpression was sufficient to induce PASMC proliferation. In vivo, adeno-associated virus 1 (AAV1)–mediated overexpression of miR-224 exacerbated PAH in mice, whereas intratracheal delivery of aerosolized AAV1–ToughDecoy–miR-224 or a chemically modified antisense oligonucleotide targeting miR-224 (LNA-224) attenuated disease severity in Sugen/Hypoxia (Su/Hx) and monocrotaline models in both mice and rats. Moreover, SMC-specific inhibition of miR-224 via an AAV1 vector expressing ToughDecoy–miR-224 reversed pulmonary vascular remodeling and improved right ventricular function in the Su/Hx mouse model. Mechanistically, miR-224 targeted multiple components of the bone morphogenetic protein (BMP)/transforming growth factor–β (TGFβ) signaling pathway, leading to suppressed BMP/SMAD signaling and enhanced TGFβ-associated responses. Inhibition of miR-224 restored the balance between growth-inhibitory BMP signaling and growth-promoting TGFβ signaling in PASMCs. Collectively, these findings identify miR-224 as a regulator of pulmonary vascular remodeling and highlight miR-224 inhibition as a promising therapeutic strategy for PAH.